Pricing and capital allocation in catastrophe insurance - Zanjani, George (Journal of Financial Economics, 2002)
This paper studies multi-line pricing and capital allocation by insurance companies when solvency matters to consumers, capital is costly to hold, and the average loss is uncertain. In this environment, product quality concerns lead firms to diversify across markets and charge high prices for risk that threatens company solvency, even if the risk is unrelated to other asset risk. Price differences across markets are traced to differences in capital required at the margin to maintain solvency. Finally, the paper shows that capital costs have significant effects on catastrophe insurance markets because of high marginal capital requirements.